Computer simulations suggest that acute correction of hyperglycaemia with an insulin bolus protocol might be useful in brain FDG PET - Buchert, R.; Santer, R.; Brenner, W.; Apostolova, I.; Mester, J.; Clausen, M.; Silverman, D. H. S. (Nuklearmedizin - NuclearMedicine, 2009)
Aim: FDG PET in hyperglycaemic subjects often suffers from limited statistical image quality, which may hamper visual and quantitative evaluation. In our study the following insulin bolus protocol is proposed for acute correction of hyperglycaemia (> 7.0 mmol/l) in brain FDG PET. (i) Intravenous bolus injection of short-acting insulin, one I.E. for each 0.6 mmol/l blood glucose above 7.0. (ii) If 20 min after insulin administration plasma glucose is ≤ 7.0 mmol/l, proceed to (iii). If insulin has not taken sufficient effect step back to (i). Compute insulin dose with the updated blood glucose level. (iii) Wait further 20 min before injection of FDG. (iv) Continuous supervision of the patient during the whole scanning procedure. Methods: The potential of this protocol for improvement of image quality in brain FDG PET in hyperglycaemic subjects was evaluated by computer simulations within the Sokoloff model. A plausibility check of the prediction of the computer simulations on the magnitude of the effect that might be achieved by correction of hyperglycaemia was performed by retrospective evaluation of the relation between blood glucose level and brain FDG uptake in 89 subjects in whom FDG PET had been performed for diagnosis of Alzheimer's disease. Results: The computer simulations suggested that acute correction of hyperglycaemia according to the proposed bolus insulin protocol might increase the FDG uptake of the brain by up to 80%. The magnitude of this effect was confirmed by the patient data. Conclusion: The proposed management protocol for acute correction of hyper glycaemia with insulin has the potential to significantly improve the statistical quality of brain FDG PET images. This should be confirmed in a prospective study in patients.
Keywords: [18F]fluorodeoxyglucose FDG; hyperglycaemia; brain; insulin; image quality